INTRA-SPESIFIC DIVERSITY OF BUTTERFLY PEA (Clitoria ternatea L.) REVEALED BY ISSR WITH INVARIABLE ITS RECORDS - Adib Fakhruddin Yusuf; Vida Rahma Latifah; Vivi Indah Nurcahyati; Anggun Diyan Nurhasanah; Adristi Shafa Widyasari; Ananto Puradi Nainggolan; Aldy Riau Wansyah Hasibuan; Madyan Akmal Hidayat; Karmilah; Arini Dian Pratiwi; Rindu Aurantika; Muslifah Hasanah; et al. (Biotropia: The Southeast Asian Journal of Tropical Biology)
Article Highlights: - The ITS region exhibits no genetic variation among butterfly pea genotypes. - ISSR reveals high polymorphism, proving effective for genetic diversity analysis. - White single and purple single genotypes show the greatest genetic distance. - ISSR-6 ((CT)₈TG) demonstrates the highest polymorphism and reliability for assessment. - The ITS sequences have been deposited in GenBank under the accession IDs PQ198055–PQ198061.